PENGARUH VARIABEL SOSIAL, KEPRIBADIAN, KONTROL DIRI, JENIS KELAMIN, DAN UANG SAKU TERHADAP KEPUTUSAN BELANJA ONLINE REMAJA DI KOTA DENPASAR - Surya Dharma, I Kadek Adjus; Santika, I Wayan (E-Jurnal Manajemen, 2014)
Shopping online is not a new thing for Internet users where Internet users are spoiled with the convenience offered by online entrepreneurs. The number of online entrepreneurs make in the field of online business competition is getting tight, so it takes the right strategy in order to compete in the online business. The purpose of this study was to determine the effect of variables that influence online shopping decisions of teenagers in the city of Denpasar and which variables dominate the online shopping decision teenager, so that marketers can implement appropriate strategies by observing the influential variables. Multiple linear regression analysis as a data analysis technique, with 100 respondents as the study sample. The analysis showed that all variables have a significant effect, with the dominant influence of social variables. Family, group interaction, and social status of adolescents should be of particular concern that marketers use marketing strategies that are expected to provide a positive influence to the target market. Key words : purchasing decisions, shopping behavior